Judicial practice (Journal of actual problems of jurisprudence, 2018)
Actuality of the article is that the legal science and the practice of recent decades show increasing interest raise questions concerning the conceptualization of the principle of separation of powers, defining the status of the judiciary. The object of the article is a relationship existed during the enforcement of judicial organs, during which are born regulatory controls. The subject o the article are law statuses creating by judicial practice.Key words: judicial practice, judicial power, judicial precedens,Supreme Court of the Republic of Kazakhstan, normative decisions.